2009
DOI: 10.1016/j.jaci.2008.11.032
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity, serum lipid levels, and allergic sensitization in Chinese men and women

Abstract: Background-Obesity and allergic diseases have increased dramatically in recent decades. While adiposity has been associated with asthma, associations with allergic sensitization have been inconsistent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 30 publications
1
39
3
Order By: Relevance
“…In 2 studies, overweight subjects were found to be significantly more prone to sensitization to food allergens than normal-weight subjects [42,43,44]. IgE levels in blood serum were elevated as well as the levels of CRP, showing that obesity might indeed be linked to increased sensitization [43,44].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2 studies, overweight subjects were found to be significantly more prone to sensitization to food allergens than normal-weight subjects [42,43,44]. IgE levels in blood serum were elevated as well as the levels of CRP, showing that obesity might indeed be linked to increased sensitization [43,44].…”
Section: Resultsmentioning
confidence: 99%
“…IgE levels in blood serum were elevated as well as the levels of CRP, showing that obesity might indeed be linked to increased sensitization [43,44]. Especially in the age group of 2- to 5-year-olds, the risk for food sensitization was particularly strong.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the risk of allergic sensitization increased with lower HDL and higher LDL levels [48], especially in females. Therefore, it has been hypothesized that contrasting reports on the association between serum cholesterol and atopy and confounding factors could be the expression of differences in race and/or other demographic variables.…”
Section: Resultsmentioning
confidence: 99%
“…Asthma is a systemic inflammation, and multiple mechanisms and biomarkers such as high-sensitivity C-reactive protein [32], tumor necrosis factor-伪, IL-6, IL-8 [33] and fibrinogen [34] have been associated with this disease, which are not necessarily specific to the Th2 immunity profile and atopy. Another possible explanation for the link between asthma and HDL-C is the share of a common genetic influence between low HDL-C and allergic sensitization, as suggested in a report in 1,187 Chinese twins [35]. In the setting of a genetic link between low HDL-C and allergic sensitization, common adverse environmental influences (e.g.…”
Section: Discussionmentioning
confidence: 99%